Differences in the Effect of Circuit Training and Fartlex Training on Increasing Vo2Max of Pencak Silat Athletes - Kamarudin Kamarudin; Sasmarianto Sasmarianto; Wahyuni Rahmalia (Indonesian Journal of Physical Education and Sport Science, 2024)
Study Purpose. The purpose of this study was to determine the difference in the effect between circuit training and fartlek training in increasing VO2Max for pencak silat athletes.